Contribuição para uma estratégia para criação de áreas marinhas protegidas em Angola - Safeca, Albertina Cainara Lima (2020)
The world’s seas, its resources and the services they provide have been of great value to society as a whole, however, over the centuries the rapid loss of species and their habitats has been cause for concern, leading to the introduction of mechanisms to save marine biodiversity. There has been in recent years an increase in the number of marine protected areas implemented worldwide and Angola has as part of its political agenda, the creation of marine protected areas as a mean to stop the loss of its marine biodiversity. This dissertation will serve as contribution for the work carried out by the Angolan authorities on the creation and management of marine protected areas.